Sosialisasi penyemaian bibit dari buah Enhalus acoroides untuk menjaga keberlanjutan ekosistem Lamun di Desa Pengudang Pulau Bintan - Ita Karlina; Aditya Hikmat Nugraha; Dony Apdillah; Jelita Rahma Hidayati; Esty Kurniawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Seagrass ecosystems contribute to food security, climate change mitigation, and biodiversity, yet they are vulnerable to changes in the environment. Environmental factors, both natural and human-caused, are the primary cause of the loss in the area of seagrass ecosystems. Transplanting or sowing seagrass is one method for addressing this issue. The goal of this project is to maintain the seagrass environment and give coastal people with knowledge so that they may contribute to the conservation of coastal habitats, particularly seagrass ecosystems, in Pengudang Village, Bintan. The seeding process starts with a search for seagrass in areas with a dense seagrass habitat. Enhalus acoroides was chosen as the seeding object in this investigation. The findings revealed that 78% of respondents were highly aware of the existence of seagrass ecosystems (perception), 28% were very aware of the function and existence of seagrass ecosystems (understanding), and 86% significantly participated in seagrass ecosystem conservation (participation).